PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN PARTISIPASI BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN IPA KELAS IV SD NEGERI 124388 PEMATANGSIANTAR - Simanjuntak, Melvin; Roi Simanjuntak; Mei Evelina Sitohang; Rolita Dolok Saribu; Christian Silaban; Christian Stevani Sihaloho; Yohana Panjaitan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effectiveness of implementing the demonstration method in increasing the learning participation of grade 4 elementary school students in science learning. The method used in this research is qualitative using data collection techniques through observation, interviews and documentation. The research results show that the application of the demonstration method can increase the learning participation of grade 4 elementary school students in science learning. This is evidenced by an increase in students' active participation in learning, and an increase in students' interest in learning science. This research has several important implications. First, this research shows that the demonstration method is an effective method for increasing student learning participation in science learning. Second, this research contributes to the development of more effective and innovative learning strategies, especially in science learning. Third, this research provides insight for educators in improving the quality of science learning in elementary schools.